DIAGNOSTIC OPPORTUNITIES OF NEUROOPHTHALMOLOGIC INSPECTION AT RS: ROLE OF AN OPTICAL COHERENT TOMOGRAPHY AND THE VISUAL CAUSED POTENTIALS IN EARLY DIAGNOSTICS OF MULTIPLE SCLEROSIS AND MONITORING OF A CONDITION OF THE VISUAL ANALYZER AT PATIENTS WITH VARIOUS OPTIONS OF MULTIPLE SCLEROSIS - Ye. A. Andreyeva (Бюллетень сибирской медицины, 2013)
Examination of 70 patients with different options of a course of multiple sclerosis is conducted. Reliable decrease in thickness of a layer of a neuroepithelium and macular volume of a retina at patients with various options of a course of the multiple sclerosis, more expressed is noted at primary progressing and secondary progressing current options, and the patients who have transferred an optical neuritis. The functional violations at the level of an optic nerve according to the visual caused potentials – increase in a latence and decrease in amplitude of the P100 component are revealed. Possibility of application of methods of an optical coherent tomography and the visual caused potentials for diagnostics and monitoring of pathological process is shown at multiple sclerosis.